ELEVATED EARLY CHILDREN'S CREATIVITY THROUGH DIFFERENTIATE LEARNING - yunita yunita; Irma Yuliantina; Johana Kastanja; Yunita Damayanti; Anna Jacob; Heny Haryanti (Universitas Panca Sakti Bekasi, 2023)
The prevalence of conventional learning carried out by teachers where learning is still teacher-centered results in low child creativity, an approach that encourages increased child creativity is needed. One approach that allegedly increases children's creativity is through a differentiated learning process. Creativity is generating new ideas, solving problems, and thinking outside conventional boundaries. Differentiated learning is a strategy in which all children have the same learning goals, but teachers vary teaching methods to meet children's needs and vary the complexity of tasks and learning support for each child. Through this approach, teachers can design learning experiences that are relevant, challenging, and interesting for children. Differentiated learning can increase creativity in early childhood; First, this approach allows the teacher to understand each child's individual needs and provide appropriate support. Second, by emphasizing diverse learning experiences, children have the opportunity to develop their imagination, develop new ideas, and overcome creative challenges. The purpose of this paper is to analyze how to create differentiated learning strategies that can be used to increase creativity in early childhood. This study used a descriptive qualitative method. Differentiation learning encourages teachers to use interesting materials, organize creative learning spaces, provide challenges that are appropriate to the child's developmental level, and provide positive and constructive feedback. Through a differentiated learning approach, children can develop their creative potential from an early age, which will positively impact their future development.